The Role of Short Film-Based Creative Media on Understanding Financial Literacy for Achieving SDGs 4.6 Universal Literacy and Numeracy in Indonesia - Hasna Nabilah Rahma; Rahma Nadia Safitri; Revy Rafsanjani Putra Arfandy; Maclaurin Hutagalung; Eksa Pamungkas (The Indonesian Institute of Science and Technology Research, 2026)
Financial literacy is one of the essential elements that must be improved to achieve the Sustainable Development Goals (SDGs) in Indonesia, particularly SDG 4.6, which targets the attainment of literacy and numeracy by 2030. This study examines the role of creative media, specifically short films, in enhancing financial literacy understanding, particularly among individuals aged 15 to 40 years. A quantitative approach was employed, utilizing a one-group pretest-posttest design with 80 respondents. Data were collected through multiple-choice and short-answer questionnaires and analyzed using the Wilcoxon Signed-Rank Test and sentiment analysis based on the Bidirectional Encoder Representations from Transformer (BERT) model. The results indicated that the short film intervention had a significant impact on participants' understanding (p = 0.08, p < 0.1), which was further validated through sentiment analysis with high model accuracy (≥ 90%). Interestingly, a slight posttest decline in self-perceived knowledge, despite improvements in behavior, suggests a metacognitive shift aligned with the Dunning-Kruger effect. Increased exposure to financial concepts likely helped participants more accurately recognize their prior misconceptions and knowledge gaps. This reflected a meaningful cognitive shift from overconfidence to self-awareness, which was essential for sustained learning and sound financial behavior. Results also confirmed that creative media could both educate and influence perception, making it a valuable approach for improving financial literacy and supporting SDG 4.6. The findings of this study are expected to serve as a reference for stakeholders in designing similar initiatives.